The type species of the genus Geotrygon Gosse, 1847 (Aves: Columbidae) - Mlíkovský, Jiří (Zootaxa, 2016)
The generic name Geotrygon was introduced by Gosse (1847: 316) for some doves from the island of Jamaica and has been subsequently used for the so-called quail-doves of Middle and South America (Baptista et al. 1997; Gibbs et al. 2001; Dickinson 2003; Dickinson & Remsen 2013). Johnson & Weckstein (2011) and Banks et al. (2013) indicated that this genus is polyphyletic. The application of a generic name is determined by its type species (Art. 42.3 of the International Code of Zoological Nomenclature; ICZN 1999; hereafter the Code). A literature search showed that different nominal species have been proposed as the type species of Geotrygon, and the situation thus requires clarification.